Rapid detection of microbial contamination on food contact surfaces in restaurants with long operating hours using mobile flow cytometer - Shafizi Abdul Wahab; Alia Aryssa Mohd Haris; Chai, Lay Ching; Nurul Aqilah Mohd Zaini; Mohamad Yusof Maskat; Chok, Hui Mei; Huda Saber Abu Bakar Saleh; Mohamed Yusuf Mohamed Nazir; Sahilah Abdul Mutalib (Penerbit Universiti Kebangsaan Malaysia, 2025)
Cross-contamination on food contact surfaces (FCS) increases the risk of foodborne diseases incidence. Traditional microbial detection methods are time-consuming, prompting the exploration of the rapid method; CytoQuant® mobile flow cytometer which employ perturbation of low-frequency electric fields between intact membrane and cytoplasm. The cross-sectional study used CytoQuant® and total plate count (TPC) involved 30 FCS from six (n = 6) selected restaurants with long operating hours in the Lembah Klang area. Findings showed that the CytoQuant® was able to detect the presence of microbial contamination within 30 seconds without pre-treatment. The results also showed that there were significant differences (p < 0.05) between intact cell and particles readings on FCS. Furthermore, even though there are some differences in individual sample readings from the FCS, the mean values across various restaurants showed no significant difference (p > 0.05) between CytoQuant and TPC, suggesting that both methods provide comparable intact cell measurements on average. Further microbiological and premise rating analysis showed that all six premises exhibited aerobic, coliform counts and patogen exceeding established thresholds on the cutting board, including detection of salmonella in one of the premises, which correlated with the poor premises rating. This study suggest that employing CytoQuant® on-site ensures rapid and reliable results in monitoring of FCS, reducing the risk of foodborne diseases compared to TPC analysis.